DEVELOPMENT ASSESSMENT OF ALTERNATIVE PRACTICUM II BASIC CHEMICAL THROUGH CHEMISTRY FAIR PROJECT ( CFP ) BASED CONSERVATION USING CHEMICAL DAILY - Wusqo, I. Urwatin; Taufiq, M.; Handayani, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This study aims to (1) develop an alternative assessment on the 2nd General Chemistry Experiment through conservation-based chemistry fair project by utilizing the daily chemical (2) Determine the level of validity, practicality and effectiveness. This research is the development (Research Development) development model applied Dick and Carey (1985). The subject of limited testing and field trials is subject lecturers and students of Science Education UNNES. Determined by purposive sample, the lecturers and the students who take the course 2nd General Chemistry Experiment. The data obtained from this trial are: (1) input from experts, to determine the content and construct validity of the assessment feature; (2) input from a limited sample testing, to determine the practicality of chemistry clue fair project (CFP) based conservation by utilizing chemical daily; Instrument data collectors in the form of a questionnaire legibility chemistry making instructions fair project (CFP) based conservation by utilizing daily chemical, scoring guidelines. (3) student learning outcomes data to determine the effectiveness of the assessment. Input from experts student questionnaire, and the value of chemistry fair project (CFP) limited test samples analyzed qualitatively and quantitatively. Assessment of 2nd General Chemistry Experiment alternative developed is successful well-developed assessment if valid, practical, and effective.